منهج الإمام الأزهري في توجيه القراءات من خلال كتابه )معاني القراءات( Al-Azhari’s approach on the guidance of the modes of recitation through meaning of the modes of recitations book - Mohd A'tarahim, Mohd Razali; Mohamed Fathy, Mohamed Abdelgelil (2019)
Kitab Ma’ani Al-Qira’at (meanings of the modes of recitations) by Al-Azhari encompasses a valuable scientific content on the guidance of the modes of recitation. It is considered one of the earliest books written on the guidance on the modes of recitation. Having inducted this book, the researcher concluded that Al-Azhari had followed many methods on the guidance of the modes of recitation, and his approach needs to be studied and clarified. As is well known, each author has his or her own approach, Given this point of departure, the author has conducted this research for the purpose of exploring Al-Azhari’s approach on the guidance of the modes of recitation, and showing the features and tools utilised for that purpose in terms of guiding the modes of recitation by the Holy Quran, the Prophet’s Hadith, othmanic text/ Ottoman lettering, verse etc. The author has followed the analytical inductive approach, where he has inducted Kitab Ma’ani Al-Qira’at (the meanings of the modes of recitation book) finding out the guidance features and tools employed by Al-Azhari for that purpose. This study found out many results: Al-Imam Al-Zuhri did not rely heavily on both the Prophet’s Hadith and Othmanic text /Al-Rasim Al Othmani / Ottoman lettering). He also ignored guiding the successive modes of recitation by the shadhdh ones (without a successive transmission). However, he relied heavily on verse and Arabs sayings and dialects. This study also concluded that Ma’ani Al-Qira’at by Al-Azhari has a considerable scientific value, but it needs refinement and editing because it contains some of weak viewpoints which dispute the validity of some modes of recitation without reacting to them/ with impunity.